2022
DOI: 10.1097/mpg.0000000000003490
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Novel High-Quality Protein Infant Formula on Energetic Efficiency and Tolerance: A Randomized Trial

Abstract: Objectives: Protein overfeeding in infants can have negative effects, such as diabetes and childhood obesity; key to reducing protein intake from formula is improving protein quality. The impact of a new infant formula [study formula (SF)] containing alpha-lactalbumin, lactoferrin, partially hydrolyzed whey, and whole milk on growth and tolerance compared to a commercial formula (CF) and a human milk reference arm was evaluated. Methods: This randomized, double-blind trial included healthy, singleton, term inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
(73 reference statements)
2
5
0
Order By: Relevance
“…First and foremost, similar results were found in the study by Karaglani et al, which assessed the effects on growth parameters of a pHF compared to an IPF in 163 healthy formula-fed infants over a period of three months (19). Similarly, other previous studies investigating the effects of different pHFs on growth indices of infants as compared to intact protein-based formulas or breast milk have found no differences among the study groups (20)(21)(22)(23). Moreover, during the 10-year follow-up of the German Infant Nutritional Intervention Study (GINI) no differences were observed in weight, length and BMI gains of infants with atopic heredity fed with either a partially hydrolysed formula, an extensively hydrolysed formula, a cow's-milk based formula or breast milk (24,25).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…First and foremost, similar results were found in the study by Karaglani et al, which assessed the effects on growth parameters of a pHF compared to an IPF in 163 healthy formula-fed infants over a period of three months (19). Similarly, other previous studies investigating the effects of different pHFs on growth indices of infants as compared to intact protein-based formulas or breast milk have found no differences among the study groups (20)(21)(22)(23). Moreover, during the 10-year follow-up of the German Infant Nutritional Intervention Study (GINI) no differences were observed in weight, length and BMI gains of infants with atopic heredity fed with either a partially hydrolysed formula, an extensively hydrolysed formula, a cow's-milk based formula or breast milk (24,25).…”
Section: Discussionsupporting
confidence: 83%
“…In addition, similar stool consistency was found between the two groups except for a slightly higher percentage of watery stools observed in the pHF group at 17 weeks of age (23). Kuehn et al observed softer mean stool consistency in the infants fed with whey-casein pHF compared to the infants fed with a commercial non-hydrolysed whey-casein formula (20). So, several clinical studies have now indicated that consumption of partially hydrolysed proteins by healthy infants may affect stools, and result in a lower stool consistency score compared to a formula containing intact protein only.…”
Section: Discussionsupporting
confidence: 53%
“…The 7-year BeMIM follow-up data suggested that feeding infants with an intervention formula with reduced protein content and added α-lactalbumin enriched whey and long-chain polyunsaturated fatty acids during the first four months of life was safe and did not lead to differences in anthropometry or the occurrence of serious illnesses up to early school age. The importance of such a long-term follow-up of children who were fed infant formulas with different energetic efficiency was emphasized by a recent study that compared a standard infant formula with a formula with improved composition, including the inclusion of α-lactalbumin enriched whey, lactoferrin and whole cow’s milk [ 32 ]. In agreement with BeMIM during the intervention period until the age of 24 weeks, higher energetic efficiency for growth was observed for the investigational formula [ 32 ], which might suggest that higher energetic efficiency is linked to improved protein quality.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of such a long-term follow-up of children who were fed infant formulas with different energetic efficiency was emphasized by a recent study that compared a standard infant formula with a formula with improved composition, including the inclusion of α-lactalbumin enriched whey, lactoferrin and whole cow’s milk [ 32 ]. In agreement with BeMIM during the intervention period until the age of 24 weeks, higher energetic efficiency for growth was observed for the investigational formula [ 32 ], which might suggest that higher energetic efficiency is linked to improved protein quality. Further formulas with lower protein content, but of higher quality, can be expected; therefore, it is reassuring that the 7-year BeMIM follow-up did not find any indications of negative effects of such formulas.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere in this issue, Kuehn et al (3) report an infant formula feeding trial. At a time of infant formula shortages, a new domestic manufacturer of infant formula is welcome (4).…”
mentioning
confidence: 99%